2017
DOI: 10.1002/slct.201701173
|View full text |Cite
|
Sign up to set email alerts
|

Role of Halide Ions for Controlling Morphology of Copper Nanocrystals in Aqueous Solution

Abstract: This paper reports the influence of halide ions on the morphology-controlled synthesis of Cu nanocrystals in the aqueous phase. Cu nanocrystals with controlled shapes, including 2D plates, 1D wires, and 3D polyhedral particles were obtained by a reduction reaction between Cu-halide and ascorbic acid, and branched polyethyleneimine (BPEI) was used as a stabilizing agent in the process. Density functional theory (DFT) calculations showed that this morphological control was caused by the selective adsorption of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…Typically, because Cu can be easily oxidized by water and oxygen in the air, and its reduction potential is very different from the reduction potential of Pt or Ag, it is difficult to synthesize a Cu-based alloy compared with Ag-based alloy nanoparticles in an aqueous phase [25,26]. In a previous report on the aqueous-phase synthesis of Cu nanocrystals with long-term stability in air, it was demonstrated that BPEI formed a Cu-BPEI complex, thus leading to the formation of stable Cu nanocrystals in an aqueous phase [27,28]. In the present synthesis, we attempted to synthesize CuPt nanoparticles in We also investigated the synthesis of AgPd nanoparticles by using BPEI, L-ascorbic acid, AgNO 3 , and Na 2 PdCl 4 as similar synthetic conditions for AgPt nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…Typically, because Cu can be easily oxidized by water and oxygen in the air, and its reduction potential is very different from the reduction potential of Pt or Ag, it is difficult to synthesize a Cu-based alloy compared with Ag-based alloy nanoparticles in an aqueous phase [25,26]. In a previous report on the aqueous-phase synthesis of Cu nanocrystals with long-term stability in air, it was demonstrated that BPEI formed a Cu-BPEI complex, thus leading to the formation of stable Cu nanocrystals in an aqueous phase [27,28]. In the present synthesis, we attempted to synthesize CuPt nanoparticles in We also investigated the synthesis of AgPd nanoparticles by using BPEI, L-ascorbic acid, AgNO 3 , and Na 2 PdCl 4 as similar synthetic conditions for AgPt nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…Also noteworthy, is that while most syntheses derive Cu 2+ from CuCl 2 as opposed to Cu(NO 3 ) 2 , its substitution into our reaction scheme yields unsatisfactory results in that only small protrusions grow off an otherwise spherical seed (Figure S2, Supporting Information). Chlorine ions are known to influence growth modes involving both Cu and CuO 2 . The resulting Cu templates, which are shaped as a substrate‐truncated cuboctahedrons, are highly faceted, displaying three prominent square (100) facets and four (111) facets.…”
Section: Resultsmentioning
confidence: 99%
“…Tang et al demonstrated the influence of halide ions on the morphology-controlled synthesis of Cu nanocrystals in the aqueous phase. 88 The type of halide ion (Cl − , Br − , I − ) solely controlled the morphology of nanocrystals (2D plates, 1D wires, and 3D polyhedral particle). DFT study showed that the co-adsorption strength of ammonium and halide ions on Cu(100) compared to Cu(111) was a critical factor in regulating the shape of the Cu NCs.…”
Section: Growth Mechanismmentioning
confidence: 99%